Discretion and control at the front line : rationalities of practice in child and youth services - Halfpenny, Nicholas (Curtin University, 2011)
Focusing on child and youth services in Victoria this research is a theoretical conceptualisation of the governance of front line work. The research addresses the question of how multiple rationalities of practice are experienced by front line workers. In exploring the contemporary context for practice, the research provides an analysis of the history and development of non-government organisations and human service professions and their roles in delivering publicly funded welfare services.The discursive practices associated with the concepts of managerialism and contractualism are explored in terms of how front line work is configured and controlled. The research combines a critical examination of two modalities of surveillance and control of front line work (the Registration Standards for Community Service Organisations and the Looking After Children Framework). These case examples are positioned as exemplars of modalities of surveillance and control that represent contemporary administrative and managerial logics. I offer a detailed analysis of the interplay between these instruments and particular logics of social work practice.The concepts of governmentality (Foucault, 1991) and habitus (Bourdieu, 1990) are developed to articulate a more embodied understanding of human service practice where interpretation is positioned at the centre of action. Using material collected from interviews with front line staff, the concept of habitus is further expanded to articulate an understanding of practice that explores how multiple rationalities are configured and enacted. The analysis positions the embodied histories of individual front line workers as the key influence in the construction of practice.This analysis addresses a significant gap in the understandings of work in the human services and contributes a new and critical understanding of the instruments of control and discretionary practice in the human services. The research concludes with a consideration of pathways to enact a practice that critically engages with contemporary modalities of governance.